2019
DOI: 10.1186/s12889-019-6677-5
|View full text |Cite
|
Sign up to set email alerts
|

Trends in heterosexual inexperience among young adults in Japan: analysis of national surveys, 1987–2015

Abstract: Background It has been suggested that an increasing number of Japanese adults remain sexually inexperienced; however, no study has assessed this issue using nationally representative data. Methods We used data from seven rounds of the National Fertility Survey of Japan, 1987–2015, and included adults aged 18–39 years (18–34 years in the 1987 survey) in the analyses (sample size 11,553–17,850 [1987–2010]; response rate 70.0–92.5%). For each survey year, sex and age group… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
27
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 31 publications
(33 citation statements)
references
References 20 publications
1
27
0
1
Order By: Relevance
“…The middle-aged men from Kanto, Kinki, and Chubu regions had significantly higher odds of primary sexual abstinence than those from the other regions (Kyushu, Chugoku, Tohoku, and Hokkaido). 39 A further study reported that young men living in urban areas had significantly lower odds of primary abstinence than those living in rural areas. 32 It was also reported that living in densely populated areas and in a neighborhood with the social disorder (fight by using weapons) had a significantly negative relationship with primary sexual abstinence in men.…”
Section: Socioeconomic Statusmentioning
confidence: 95%
See 4 more Smart Citations
“…The middle-aged men from Kanto, Kinki, and Chubu regions had significantly higher odds of primary sexual abstinence than those from the other regions (Kyushu, Chugoku, Tohoku, and Hokkaido). 39 A further study reported that young men living in urban areas had significantly lower odds of primary abstinence than those living in rural areas. 32 It was also reported that living in densely populated areas and in a neighborhood with the social disorder (fight by using weapons) had a significantly negative relationship with primary sexual abstinence in men.…”
Section: Socioeconomic Statusmentioning
confidence: 95%
“…Primary sexual abstinence in young men 11e14,16e20, 22,29e33,39e42 and middle-aged men ranged from 3.4% to 83.3% and 5.5%e32.8%, respectively. 11,39 Furthermore, the age categorization given in the selected studies showed that the prevalence for 10-to 19-year-old men was the highest (27.7%e 83.3%), 12,13,16,18,22,30,33,39 followed by 15-to 24-year-old men (3.4%e59.7%) 13,14,16,17,19,31,32,39,41 and 25-to 45-year-old men (5.5%e32.8%) 11,39 (Table 1). Table 1 shows that the overall prevalence of secondary abstinence reported in 22 studies ranged between 0% and 83.6% in men younger than 60 years ( Table 1).…”
Section: Primary Sexual Abstinencementioning
confidence: 99%
See 3 more Smart Citations